Nasogastric tube insertion in anesthetized, intubated adult patients: A comparison between conventional blind insertion technique and “throat pack in situ” technique - Roy, Vaskar; Maitra, Sanjay; Mandal, Sangita; Chakraborty, Soma; Arpita Laha; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2023)
Background: Correct placement of nasogastric tube (NGT) placement often becomes difficult in anesthetized, intubated adult patients due to lack of cooperation from patient and the propensity of the tube to travel the same course of path. Preexisting throat pack is supposed to resist the normal passage of the NGT as per common belief. Only one study has evaluated this in pediatric population and the result is encouraging. Aims and Objectives: Hence, the present study has been carried out in adult population to compare the success rate of correct placement of NGT in anesthetized intubated adult patients with the pharyngeal (throat) pack in its position in comparison with no throat pack. This is to examine the effect of preexisting throat pack whether it assists or resists the normal passage of the NGT. Materials and Methods: One hundred and eighty patients were recruited for this interventional and single-blind study. After induction of anesthesia and intubation, the patients were randomized to receive NGT insertion following either blind insertion of the NGT without a pharyngeal pack (group A, n=90) or receive the NGT placement in the same technique but after placement of a pharyngeal pack. The success rate of correct placement of NGT in the first attempt (primary outcome), the procedure time, and adverse events was recorded. Results: Successful insertion of NGT in first attempt was considerably higher in throat pack in situ group compared to blind insertion without a throat pack 81 (90%) versus 63 (70%), respectively (P=0.001). The procedure time for successful placement of NGT was found comparable between the two groups. Significant decrease in coiling is seen in “throat pack in situ” group compared with blind insertion technique (P=0.003). Conclusion: In view of considerable higher success rate and reduced adverse events, it can be concluded that the pre-existing appropriately placed throat pack can facilitate the placement of NGT instead of putting any hindrance.